Proyecto de pasantía “Plan estratégico de mercadeo nacional e Internacional para el turismo sostenible en Soatá, Boyacá” (2023)
This work analyzes through a strategic plan of national and international marketing the different internal and external economic, social and cultural factors identifying the opportunities, threats, weaknesses and strengths presented by tourism in Soatá, Boyacá, in order to formulate and implement digital marketing strategies that allow you to achieve economic development, positioning and increasing competitiveness in today's market.